Zarafshan Water District improvement project in Uzbekistan - Nazarov, Azimjon S., author; Karimov, Askarali, author; Fipps, Guy, author; U.S. Committee on Irrigation and Drainage, publisher (Colorado State University. Libraries, 2005)
Irrigation plays an important role in the economy of Uzbekistan with almost ninety percent of the cropland irrigated. Fifty percent of the irrigated area in Uzbekistan is already affected by water logging and/or salinization. Zarafshan and other Soviet-built irrigation schemes are in disrepair and not functioning efficiently. Crop losses and high operating costs ensue. Water flow information and communications systems are unreliable, forcing scheme administrators to make management and operational decisions based on insufficient information. The Zarafshan Water Districts Improvements project is design to be a model program that will guide the rehabilitation of other irrigation districts in Central Asia. This paper describes this program and what lessons have been learned to date.
Zarafshan Water District, Uzbekistan
Not digitized by CSUL Digital Services.
Presented during the Third international conference on irrigation and drainage held March 30 - April 2, 2005 in San Diego, California. The theme of the conference was "Water district management and governance."
Keywords: irrigation scheme; rehabilitation; modernization; Uzbekistan; Aral Sea basin; Central Asia